A térkapcsolatok értelmezésének néhány összefüggése - Mészáros, Rezső (Tér és Társadalom, 1989)
The field of geographical resesarch is getting wider and wider, but the system of interactions expressing spatiality – which can be derived by plays a central role in understanding the nature of geography. These three dimensions of geography are related to each other though it is often attempted to separate them whenever or the other dimension is overemphasized. It is probably the most important renewed recognition of the past one or two decades that the interaction between man and environment should be investigated in a spatio-temporal continuity. This resulted in new approaches to several geographical issues. Hagerstrand’s time geography is certainly the most outstanding among them. The present paper provides details of time geography approach for Hungarian readers.